FGF21 upregulation by hepatitis C virus via the eIF2α-ATF4 pathway: implications for interferon signaling suppression and TRIM31-mediated TSC degradation - Liu, Liang; Ito, Masahiko; Sakai, Satoshi; Liu, Jie; Ohta, Kazuyoshi; Saito, Kenji; Nakashima, Kenji; Satoh, Shinya; Konno, Alu; Suzuki, Tetsuro (Frontiers in Microbiology, 2024)
Hepatitis C virus (HCV) infection is a major cause of chronic liver diseases, known to induce endoplasmic reticulum (ER) stress, which alters cellular homeostasis and metabolic processes. While ER stress is implicated in HCV-related diseases, its precise role remains unclear. This study identifies fibroblast growth factor 21 (FGF21) as a key host factor significantly upregulated by HCV infection. Mechanistic analyses reveal that the activation of the FGF21 promoter by HCV is primarily mediated by the transcription factor ATF4, which is upregulated through the phosphorylation of eIF2α induced by ER stress. Additionally, CREBH activation further enhances ATF4 expression, contributing to increased FGF21 levels. TRIB3, upregulated by ATF4, acts as a negative regulator of FGF21 expression. The study also identifies FGF21-dependent upregulation of SOCS2 and TRIM31 in HCVinfected cells. SOCS2 contributes to the suppression of type 1 interferon signaling, aiding viral persistence, while TRIM31 promotes the degradation of the tumor suppressor protein TSC, activating the mTORC1 pathway and potentially promoting liver cell proliferation. These findings suggest that FGF21 upregulation in HCVinfected cells may play a role in both immune response regulation and cell proliferation, contributing to sustained viral infection and disease progression. Keywords：Hepatitis C virus; FGF21; ATF4; CREBH; TRIM31; SOCS2; ER stress.